SOCIAL ORIENTATION OF CULTURAL AND EDUCATIONAL PROJECTS IMPLEMENTED IN CULTURAL INSTITUTIONS OF MOSCOW - Aksenova, Sophia; Anufriev, Evgeny; Limanov, Semyon; Murzak, Irina; Oparina, Nina (Revista Inclusiones, 2020)
State cultural institutions play a crucial role in the process of forming and meeting the cultural needs of society, as well as creating conditions and technologies necessary for the personal comprehensive development and creative self-realization, ensuring active cultural and leisure activities of citizens and maintaining the proper level of culture as a material and spiritual human environment. For these purposes, socio-cultural projects of a different character and for different audiences are developed and implemented, which have become widespread in Russia in recent decades. The object of the research is the cultural and educational projects implemented in Moscow in the 2000s. The work used theoretical and empirical research methods. Theoretical methods include review and generalization of scientific and methodological literature and project documents, the experience of forming and implementing socio-cultural projects in cultural institutions of Moscow, while empirical methods are practical participation in events and projects of cultural institutions and development of socio-cultural programs. The study has concluded that the social orientation of modern socio-cultural activities is connected to the need to solve acute social problems of Russian society. Among these problems, the authors single out those that are directly related to the social well-being and physical self-preservation of the majority of Russian people, such as unemployment, low living standards, social deviations and dependencies, crime, immorality, etc.